2001
DOI: 10.1002/ajmg.10049
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of coronal craniosynostosis, Klippel-Feil anomaly, and sprengel shoulder with and without Pro250Arg mutation in the FGFR3 gene

Abstract: A unique Pro250Arg point mutation in fibroblast growth factor receptor 3 (FGFR3) was initially reported by Bellus et al. [1996: Nat Genet 14:174-176] and the phenotype subsequently by Muenke et al. [1997: Am J Hum Genet 60:555-564], Reardon et al. [1997: J Med Genet 34:632-636], and Graham et al. [1998: Am J Med Genet 77:322-329]. These authors emphasized the pleiotropic nature of this form of coronal craniosynostosis, including brachydactyly with carpal and/or tarsal coalitions, with other anomalies at lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Recent molecular genetic studies have suggested that Klippel-Feil syndrome may result from mutations or disruption of genes regulating segmentation, such as PAX1, 3 SGM1, 4 and FGFR3. 5 Vertebral segmentation occurs between the 4 th and 8 th weeks of gestation and any impairment in differentiation of the mesoderm may relate not only to cervical abnormalities but also to the combination of rare cardiovascular abnormalities such as ASV, single coronary artery, persistent left superior vena cava, patent foramen ovale and aortic valve fenestration observed in this patient. In fact, Klippel-Feil syndrome is associated with various cardiovascular abnormalities in 4-29% of patients.…”
Section: Discussionmentioning
confidence: 80%
“…Recent molecular genetic studies have suggested that Klippel-Feil syndrome may result from mutations or disruption of genes regulating segmentation, such as PAX1, 3 SGM1, 4 and FGFR3. 5 Vertebral segmentation occurs between the 4 th and 8 th weeks of gestation and any impairment in differentiation of the mesoderm may relate not only to cervical abnormalities but also to the combination of rare cardiovascular abnormalities such as ASV, single coronary artery, persistent left superior vena cava, patent foramen ovale and aortic valve fenestration observed in this patient. In fact, Klippel-Feil syndrome is associated with various cardiovascular abnormalities in 4-29% of patients.…”
Section: Discussionmentioning
confidence: 80%
“…Kallmann syndrome with hearing loss has also been reported in association with mutations in FGF8 (Falardeau et al, 2008). Moreover, a specific mutation in FGFR3 causes Muenke syndrome, consisting of coronal craniosynostosis and congenital sensorineural hearing loss (Muenke et al, 1997; Holloway et al, 1998; Lowry et al, 2001). Mutations in the tyrosine kinase domain of FGFR2 and 3 cause lacrimoauriculodentodigital syndrome (LADD), a component finding of which is mixed hearing loss (Milunsky et al, 2006; Rohmann et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Muenke syndrome (OMIM 602849) is caused by a heterozygous 749C>G transversion in FGFR3 , which changes proline 250 to arginine (17,18). This is the most common individual mutation that occurs in a craniosynostosis syndrome (19), and several reports indicate that it can be variably associated with sensorineural hearing loss (HL) (2024). In in vitro assays of the FGFR3c spliceform, the proline to arginine substitution, located in the linker between the extracellular IgII and IgIII domains of the receptor, resulted in significantly enhanced binding to two of nine tested FGFs, FGF2 and FGF9 (25).…”
Section: Introductionmentioning
confidence: 99%